ChemInform Abstract: Carbolithiation of Chloro‐Substituted Alkynes: A New Access to Vinyl Carbenoids. Issue 8 (February 2015) - Lhermet, Rudy; Ahmad, Maha; Fressigne, Catherine; Silvi, Bernard; Durandetti, Muriel; Maddaluno, Jacques
Abstract Intramolecular carbolithiation of chloro‐substituted alkynes such as (I), (III), and (V) provides access to exocyclic alkylidene carbonoids.